Mapping from space (Journal on Geoinformatics, Nepal, 2003)
Traditional mapping by photogrammetry has been successful to provide a near global coverage at the 1:200 000 scale. For the more useful scale 1:50 000 only 2/3 of the globe were covered, however, there is a serious lack of update of these maps in the developing world. Mapping from satellites can bridge the existing gap in providing timely information.The paper lists the historical development of optical and radar satellite sensors. The present high resolution satellite sensors are more expensive than aerial photography products. In the future there will be competition to existing systems by small satellite operators. Advances in digital mapping technologies have led to the efficient creation of software systems for the restitution of aerial and satellite images. Radar interferometer technology has proved useful for small scale digital elevation model creation. The advantage of using satellite data is in its integration with data from other sources.